Effect of Chloride on Tensile and Bending Capacities of Basalt FRP Mesh Reinforced Cementitious Thin Plates under Indoor and Marine Environments. (7th December 2016) - Xie, Yan; Guan, Kunhua; Lai, Lin
Abstract : This paper presented a durability experimental study for thin basalt fiber reinforced polymer (BFRP) mesh reinforced cementitious plates under indoor and marine environment. The marine environment was simulated by wetting/drying cycles (wetting in salt water and drying in hot air). After 12 months of exposure, the effects of the chloride on the tensile and bending behaviors of the thin plate were investigated. In addition to the penetration of salt water, the chloride in the thin plate could be also from the sea sand since it is a component of the plate. Experimental results showed that the effect of the indoor exposure on the tensile capacity of the plate is not pronounced, while the marine exposure reduced the tensile capacity significantly. The bending capacity of the thin plates was remarkably reduced by both indoor and marine environmental exposure, in which the effect of the marine environment is more severe. The tensile capacity of the meshes extracted from the thin plates was tested, as well as the meshes immersed in salt solution for 30, 60, and 90 days. The test results confirmed that the chloride is the reason of the BFRP mesh deterioration. Moreover, as a comparison, the steel mesh reinforced thin plate was also tested and it has a similar durability performance.